A study of the effectiveness of a detergent-based California mastitis test (CMT), using Ethiopian and Nigerian domestic detergents, for the detection of high somatic cell counts in milk and their reliability compared to the commercial UK CMT [version 2; peer review: 2 approved] - Andrew R. Peters; Ciara J. Vance; Michael J. Christian; Jack D. Rust; Johanna T. Wong; Muhammed B. Bolajoko; Fiona K. Allan; Jeimmy Suarez-Martinez (Gates Open Research, 2023)
Background:  The California mastitis test (CMT) is a simple cow-side indicator of the somatic cell count (SCC) in milk, providing a useful tool in identifying cases of subclinical mastitis in cattle. Mastitis, and in particular subclinical mastitis, is a major concern in Ethiopia and Nigeria, yet detection is challenging due to cost and access to commercial CMT reagents. Methods: Commercially available domestic detergents from Ethiopia and Nigeria were compared (n = 3 for each country) with the UK commercial CMT reagent in their ability to detect high SCC (>400,000 cells/ml milk).  Sensitivity and specificity of the CMT test were calculated for the different detergents and positive and negative predictive values were established. Results:  The average sensitivities of the tests ranged from 28-75% for the Ethiopian detergents and 68-80% for the Nigerian detergents, compared to 76% for the UK domestic detergent.  Test specificities were 84-98%, 93-97% and 96%, respectively. Conclusions:  Overall, the detergents demonstrated higher specificity than sensitivity.  Nigerian detergents performed better than the Ethiopian products, however, the study identified suitable domestic detergents from both Ethiopia and Nigeria, comparable to the UK commercial CMT reagent, and we recommend their use as alternative CMT reagents for livestock-keepers to aid in cost-effective diagnosis of mastitis.